Resistance Prediction for Hard Chine Hulls in the Pre-Planing Regime - Radojcic Dejan; Zgradic Antonio; Kalajdzic Milan; Simic Aleksandar (Polish Maritime Research)
A mathematical representation of calm-water resistance for contemporary planing hull forms based on the USCG and TUNS Series is presented. Regression analysis and artificial neural network (ANN) techniques are used to establish, respectively, Simple and Complex mathematical models. For the Simple model, resistance is the dependent variable (actually R/Δ for standard displacement of Δ = 100000 lb), while the Froude number based on volume (FnV) and slenderness ration (L/V1/3) are the independent variables. In addition to these, Complex model’s independent variables are the length beam ratio (L/B), the position of longitudinal centre of gravity (LCG/L) and the deadrise angle (β). The speed range corresponding to FnV values between 0.6 and 3.5 is analyzed. The Simple model can be used in the concept design phases, while the Complex one might be used for various numerical towing tank performance predictions during all design phases, as appropriate